Adherence of the indication to European Association of Urology guideline recommended pelvic lymph node dissection at a high-volume center: Differences between open and robot-assisted radical prostatectomy. Issue 11 (November 2015) - Schiffmann, J.; Haese, A.; Leyh-Bannurah, Sami-Ramzi; Salomon, G.; Steuber, T.; Schlomm, T.; Boehm, K.; Beyer, B.; Larcher, A.; Michl, U.; Heinzer, H.; Huland, H.; et al.
Abstract: Purpose: Contemporary adherence of the indication to European Association of Urology (EAU) guideline recommendation for pelvic lymph node dissection (PLND) at either open (ORP) or robot-assisted radical prostatectomy (RARP) at a high-volume center is unknown. To assess guideline recommended and observed PLND rates in a high-volume center cohort. Methods: We relied on the Martini-Clinic database and focused on patients treated with either ORP or RARP, between 2010 and 2013. Actual performed PLND was compared to European Association of Urology (EAU) guideline recommendation defined by nomogram predicted risk of lymph node invasion >5%. Categorical and multivariable logistic regression analyses targeted two endpoints: 1) probability of guideline recommended PLND and 2) probability of no PLND, when not recommended by EAU guideline. Results: Within 7868 PCa patients, adherence to EAU PLND guideline recommendation was 97.1% at ORP and 96.8% at RARP (p = 0.7). When PLND was not recommended, it was more frequently performed at RARP (71.6%) than at ORP (66.2%) (p = 0.002). Gleason score, PSA and number of positive biopsy cores were independent predictors for both either PLND when recommended, or no PLND when not recommended (all p < 0.05). Clinical tumor stage, age and surgical approach were also independent predictors for no PLND when not recommended (all p < 0.05). Conclusions: Adherence of the indication to EAU guideline recommended PLND is high at this high-volume center. Neither ORP nor RARP represent a barrier for PLND, when recommended. However, a high number of patients underwent PLND despite absence of guideline recommendation. Possible staging advantages and PLND related complications needs to be individually considered, especially, when LNI risk is low.